Antiarrhythmic management and implantable defibrillator use in survivors of prehospital cardiac arrest without myocardial infarction in West Yorkshire. Issue 3 (1st March 2000) - Pepper, C B; Batin, P D; Ryder, M; Bannister, J; Cowan, J C; Mackintosh, A F
Abstract : OBJECTIVE: To explore the current use of secondary preventive treatment in survivors of out of hospital cardiac arrest without myocardial infarction (primary ventricular tachycardia/ventricular fibrillation (VT/VF)) in West Yorkshire, and assess the implications of recent studies on the benefits of implantable cardioverter-defibrillators (AICD) in this context. DESIGN: Retrospective analysis of an ambulance service based database of outcome after resuscitation of out of hospital cardiac arrest and the Leeds AICD implantation database. MAIN OUTCOME MEASURES: Mortality, rate of referral for specialist investigation, antiarrhythmic treatment. RESULTS: Twelve month mortality following successful discharge after primary VF arrest was 15%. Of 53 patients with primary VF/VT, 29 apparently did not see a cardiologist during the initial admission. Amiodarone was the most widely used antiarrhythmic agent. Six patients (15%) received an AICD. During the same period 22 patients from the same catchment area received an AICD following an in-hospital cardiac arrest. CONCLUSIONS: Mortality among survivors of non-infarct related prehospital cardiac arrest remains significant, with few patients being referred for specialist investigation. The implementation of recent guidelines on AICD use in cardiac arrest survivors would have resulted in an approximate 60% increase in the total numbers of defibrillators implanted in the West Yorkshire area.